2007
DOI: 10.1002/jso.20911
|View full text |Cite
|
Sign up to set email alerts
|

Liver resection for metastases from breast cancer

Abstract: Background and Objectives: The value of liver resection for metastases from breast cancer is still controversial. This study was conducted to clarify safety and effectiveness of hepatectomy in this conditions and to identify selection criteria for patients suitable for liver resection. Methods: From January 1988 to December 2006, 39 patients underwent liver resection for metastases from breast cancer. The outcome of these 39 patients was retrospectively reviewed using a prospective database. Prognostic factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
63
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 22 publications
7
63
3
Order By: Relevance
“…Size, site or number of BCLM were not generally found to be of significance, except that >1 BCLM was a negative factor in one study [23] (table 2). In the study by Elias [24], hormone receptor status was a positive factor, but this was refuted by several other studies [20,26,31,35]. In contrast, presence of hormone receptors in the primary BC as well as in BCLM had a negative influence in the study by Lubrano [36].…”
Section: Studies Of Liver Resection (N=25)contrasting
confidence: 41%
See 2 more Smart Citations
“…Size, site or number of BCLM were not generally found to be of significance, except that >1 BCLM was a negative factor in one study [23] (table 2). In the study by Elias [24], hormone receptor status was a positive factor, but this was refuted by several other studies [20,26,31,35]. In contrast, presence of hormone receptors in the primary BC as well as in BCLM had a negative influence in the study by Lubrano [36].…”
Section: Studies Of Liver Resection (N=25)contrasting
confidence: 41%
“…Presence of EHD had a negative effect in the studies by Sakamoto and Thelen [27,35], but was not significant in other studies [20,21,31].…”
Section: Studies Of Liver Resection (N=25)mentioning
confidence: 77%
See 1 more Smart Citation
“…Local treatments of liver metastases in breast cancer patients were evaluated in some studies in the literature. Microscopically complete (R0) resection of metastases were found to be a favorable prognostic factor in multiple studies reported in the literature [19][20] ; local ablation studies produced similar results with five year survival rates reaching up to 40%. 21 Performed in small prospective studies, it has been shown that RFA is also effective.…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that nearly 30% of breast cancer patients will develop liver metastases along the duration of their disease. 1-2 Liver metastases usually develop in the terminal stage of breast Hepatic with brain 13 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) International Journal of Hematology and Oncology cancer, and are often accompanied by extrahepatic metastases. Isolated liver metastases are very rare (4%-5%).…”
Section: Discussionmentioning
confidence: 99%